Carbon fluxes from a spring wheat–corn–soybean crop rotation under no‐tillage management. Issue 3 (12th August 2022) - Liebig, Mark A.; Saliendra, Nicanor Z.; Archer, David W.
Abstract: The increase in corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] production in rainfed cropping systems of the northern Great Plains (NGP) has altered the delivery of ecosystem services from agricultural land. To date, there is limited understanding about how these crops affect the carbon (C) balance of cropping systems in the region when included in a short rotation window. This study sought to quantify C balance of a spring wheat ( Triticum aestivum L.)–corn—soybean rotation under no‐tillage management using eddy covariance (EC) techniques. Paired field sites with the same soil type near Mandan, ND, were used for the study. Annual net ecosystem production (NEP) by crop was –34, 120, and 7 g C m –2 y –1 for spring wheat, corn, and soybean, respectively. Carbon removed in grain over the rotation was less than a third of C lost by ecosystem respiration (ER) (210 vs. 674 g C m –2 y –1 ). After accounting for grain C removal, net ecosystem carbon balance (NECB) was –164, –253, and –121 g m –2 y –1 for spring wheat, corn, and soybean, respectively, with a mean NECB of –179 ± 39 g C m –2 y –1 ( P  = .043; t test for difference from zero), implying the rotation was a net C source. Time associated with active crop growth each year was 27% for spring wheat, 41% for corn, and 28% for soybean. Management strategies that lengthen the period of biomass growth may mitigate C loss from spring wheat–corn–soybean rotations in the NGP. Core Ideas: Eddy covariance methods were used to quantify CO2 fluxes from a wheat–corn–soybean rotation. Annual net ecosystem production was negative for wheat, positive for corn, and near zero for soybean. Carbon removed in grain was less than a third of carbon lost by ecosystem respiration. Net ecosystem carbon balance for the rotation was negative, implying carbon loss.